Sensitivity of ‘Monika’ Cucumis sativus seedlings to low temperature and induction of chilling tolerance - Górnik, Krzysztof (Plant Breeding and Seed Science, 2015)
The aim of the research was to investigate the chilling sensitivity of cucumber seedlings and to alleviate its negative effects by short-term shock temperature applied during seeds imbibition, before radicle protrusion. The chilling sensitivity was investigated depending on initial root length (1, 3, 5 and 7 mm) and duration of chilling exposure (0, 1, 3, 7, 14, 21 days) at 0˘C and was evaluated by measurements of roots and hypocotyls growth, electrolyte leakage and dehydrogenases activity. To assess whether short-term shock temperature applied before radicle protrusion can increase chilling tolerance in cucumber seedlings the seeds were imbibed at 25°C for 16 h, exposed to temperatures of 0; 2,5; 5; 35; 40, 45°C for 0; 0,5; 1; 2; 4 h. The obtained results indicated that cucumber seedlings sensitivity depended on duration of chilling exposure and initial root length during which the seedlings were subjected to these conditions. Chilling sensitivity were manifested by drop in the roots and hypocotyls elongation, reduction in dehydrogenases activity and membrane integrity expressed by electrolyte leakage. Seedlings with 1 mm roots was relatively tolerant to 3 days of chilling at 0°C. Their chilling sensitivity increased as roots elongated. Seedling with 3, 5, 7 mm of roots subjected to chilling suffered a subsequent 71, 75 and 81% of growth inhibition, respectively. The presented results showed that a short-term of low (0; 2,5 or 5°C) or high (35; 40 or 45°C) temperature treatments applied before radicle protrusion i.e. after 16 h of seeds imbibition significantly counteracted the negative effects of chilling on seedlings. The best results expressed by increased length and the number of roots were obtained when imbibed seeds were exposed to 45°C for 2 and 4 h. The increased chilling tolerance of cucumber seedlings induced as early as at the stage of seed imbibition, before radicle protrusion indicates on the possibility of application of this method in practice. The positive response of such treatment on cucumber chilling tolerance are discussed.